Jumping to conclusions in untreated patients with Parkinson's disease. (May 2016) - de Rezende Costa, Flavio Henrique; Averbeck, Bruno; O'Sullivan, Sean S.; Vincent, Maurice Borges; Rosso, Ana Lucia; Lees, Andrew J.; Djamshidian, Atbin
Abstract: Background: Jumping to conclusions due to impulsivity has been shown to be a sensitive marker for dopamine dysregulation and addictive behaviour patterns in treated patients with Parkinson's disease (PD). It is unknown whether drug naïve PD patients, who have never received dopaminergic therapy also have deficits in information sampling. Methods: Twenty five de novo PD patients and twenty matched healthy controls were recruited and tested on the beads task, which is a validated information sampling task to assess reflection impulsivity and a temporal discounting questionnaire. Results: Patients gathered significantly less information and made more irrational choices than matched controls. There was, however, no group difference on the temporal discounting questionnaire. Conclusions: Poor information sampling and irrational decision making may be an inherent component of the neuropsychological deficit in Parkinson's disease. These findings suggest that underlying impulsivity detected by a metric task is common in de novo PD.